Biotic stress tolerance and resistance - Park, Robert (Henry Stewart Talks, 2014)
Genetic resistance provides the backbone of integrated management, Durable resistance is achieved by combining multiple resistance genes and genetic diversity to protect against pathogen changes – The gene for gene hypothesis, The identification of new resistance genes and the monitoring of pathogen virulence for deployed resistance genes, A case study in resistance breeding: wheat rusts